Social media marketing : a strategic approach - Barker, Melissa S.; Barker, Donald I.;Bormann, Nicolas F.;Roberts, Mary Lou;Zahay, Debra (Boston, Massachusetts : Cengage Learning Asia Pte Ltd, 2017)
Prepare for a successful career in social media marketing or a related field with SOCIAL MEDIA MARKETING: A STRATEGIC APPROACH, 2E. Each chapter in this book includes a section on creating a personal brand, which is useful to current or future professionals at any stage of career development. This edition emphasizes how to use social media techniques, detailed in the book, to develop and maintain a strong personal brand. Helpful discussions also address a full range of online and offline elements you can use to create a viable personal branding strategy. You learn how to use graphical concepts to structure and strategize within what is otherwise a chaotic social media milieu. This edition summarizes many of today's best practices for marketing activities on social media platforms to assist you in functioning most effectively and dealing with the rapid change that is a hallmark of social media
Chapter 1. The role of social media marketing -- Chapter 2. Goals and strategies -- Chapter 3. Identifying Target Audiences -- Chapter 4. Rules of engagement for SMM -- Chapter 5. Social media platforms and social networking series -- Chapter 6. Microblogging -- Chapter 7. Content creation and sharing: Blogging, streaming video, podcasts, and webinars -- Chapter 8. Video marketing -- Chapter 9. Marketing on photo sharing sites -- Chapter 10. Discussion, news, social bookmarking, and Q&A sites -- Chapter 11. Content marketing: Publishing articles, white papers, and e-books -- Chapter 12. Mobile marketing on social networks -- Chapter 13. Social media monitoring -- Chapter 14. Tools for managing the social media marketing effort -- Chapter 15. Social media marketing plan
Includes index.
Keywords: INTERNET ADVERTISING